Psychometric Properties of the Slovak Version of Short Dark Triad - Radka Čopková; Leoš Šafár (European Journal of Investigation in Health, Psychology and Education, 2021)
The Short Dark Triad is a scale used to capture three aversive personality traits—Machiavellianism, narcissism, and psychopathy on the subclinical level. The present study aimed to verify the psychometric properties of the Slovak version of the Short Dark Triad scale in three studies. The first two studies aimed to examine the reliability of the scale. The aim of Study 1 was to examine the factor structure of SD3. A three-factor model consisting of three latent intercorrelated factors in a unidimensional and bifactorial model were examined on a sample of 588 participants. Study 2 aimed to test the consistency of the results over time (test–retest reliability) on the sample of 117 participants. In Study 3, convergent and divergent validity was examined on the sample of 333 participants. For both kinds of validity examination, the Slovak version of NEO-FFI was used. The internal consistency of the subscales and test results, the same as the retest results, were satisfactory. The relationships between the scales were found to be significant. Confirmatory factor analysis (CFA) results supported the original three-factor model. Significant interrelations have been established between Machiavellianism and openness, agreeableness and conscientiousness; narcissism and neuroticism, extraversion and agreeableness; psychopathy and openness, agreeableness and conscientiousness. The Short Dark Triad achieved satisfactory values of reliability and validity; therefore, it can be used on the Slovak population.